Speak Chinese, Fang Fang! - Rippin, Sally
Fang Fang came to live in Australia when she was very small and is embarrassed that her mother still doesn't speak much English. Fang Fang won't speak Chinese, even when her mother asks. However, when Fang Fang's cousin Lily comes to stay from China, Fang Fang sees things a little differently
Keywords: Australian; Children's stories; Children of minorities / Australia / Juvenile literature; Children of minorities; Australia; Chinese / Australia / Fiction; Immigrants / Fiction; Mothers and daughters / Fiction; Juvenile works; Bilderbuch